Penghayatan Ratapan dalam Liturgi: Jembatan Dilema Pengharapan Kristen dan Penderitaan Manusia - Ivana Aimee Djuharto (Jurnal Teologi Pambelum, 2023)
Inside of human life’s reality, it is undeniable that Christians will definitely experience various kind of sufferings. This causes Christian to have a dilemma between the hope taught in Christian teachings and the reality of life that has a lot of suffering. This writing explains that lamentation in liturgy can bridge the dilemma. Here, I use library research method in to explain about the topic. Firstly, this writing delves how lamentation is a necessary part in human wholeness. Then, it provides biblical explanations from the Old Testament, the figure of Jesus, and the New Testament as the basis that human’s lament is reasonable and necessary. Moving on from here, I explain the importance of embracing lamentation in the liturgy and gives examples of inserting lamentations into the liturgy. Through this writing, it is found that lamentation is a natural thing that Christians should do; lamentation can bridge the dilemma of Christian hope and human’ sufferings, so it is necessary to apply lamentation in the liturgy.